The Analysis of Company Decisions in Choosing Sukuk and Bonds Using Logit Model - Pribadi, Sukma Kukuh; Wibowo, Buddi (Economica: Jurnal Ekonomi Islam, 2019)
Sukuk has become one of alternative financing for corporate. The development of Sukuk provides the flexibility choices of company’s funding decisions that required their needs and capabilities. Sukuk market in Indonesia is the second largest in emerging East Asia in terms of size but the number of issued Sukuk lower than a conventional bond. This study aims to obtain empirical evidence that the characteristics of the company influence the decision of the company in issuing Sukuk and bonds using the logit model. The results of this study conclude: (1) leverage has a negative influence and significant (2) size of the firm has a positive influence and significant (3) fixed assets has a positive influence and significant to the decision of the company in issuing Sukuk.